2009
DOI: 10.1002/app.29958
|View full text |Cite
|
Sign up to set email alerts
|

Superficial modification in recycled PET by plasma etching for food packaging

Abstract: An oxygen plasma treatment has been used to improve the adhesion of amorphous hydrogenated carbon (a-C:H) films onto surfaces of recycled poly(ethylene terephthalate) (PET). Modifications produced by the oxygen plasma on the PET surface in chemical bonds and morphology were investigated by X-ray photoelectron spectroscopy and atomic force microscopy, respectively. Contact angle measurements were used to study the changes in the surface wettability. Adhesion of the a-C:H film onto the PET surface was investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 16 publications
1
25
1
Order By: Relevance
“…The adhesion results were contrary to previous observations that used a polar polymer (PET) as the substrate [2,5]. In those studies, pre-treating the recycled PET substrate for 2.5 minutes with oxygen plasma provided good adhesion between the substrate and the a-C:H coating layer, both before and after the accelerated aging test.…”
Section: Tape Test Measurementscontrasting
confidence: 82%
See 4 more Smart Citations
“…The adhesion results were contrary to previous observations that used a polar polymer (PET) as the substrate [2,5]. In those studies, pre-treating the recycled PET substrate for 2.5 minutes with oxygen plasma provided good adhesion between the substrate and the a-C:H coating layer, both before and after the accelerated aging test.…”
Section: Tape Test Measurementscontrasting
confidence: 82%
“…Previous studies demonstrated that these films effectively reduce the migration of possible contaminants from recycled polymer without altering the food's organoleptic properties [1,2]. The efficiency of the functional polymer barriers for food packaging is evaluated by measurements of permeability that are directly related to its adhesion to the substrate [3][4][5]. Most studies in the literature have focused on poly(ethylene terephthalate) (PET) packaging [2,[5][6][7].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations